Development of the trigeminal motor neurons in parrots: Implications for the role of nervous tissue in the evolution of jaw muscle morphology. (12th October 2013) - Tokita, Masayoshi; Nakayama, Tomoki
ABSTRACT Vertebrates have succeeded to inhabit almost every ecological niche due in large part to the anatomical diversification of their jaw complex. As a component of the feeding apparatus, jaw muscles carry a vital role for determining the mode of feeding. Early patterning of the jaw muscles has been attributed to cranial neural crest‐derived mesenchyme, however, much remains to be understood about the role of nonneural crest tissues in the evolution and diversification of jaw muscle morphology. In this study, we describe the development of trigeminal motor neurons in a parrot species with the uniquely shaped jaw muscles and compare its developmental pattern to that in the quail with the standard jaw muscles to uncover potential roles of nervous tissue in the evolution of vertebrate jaw muscles. In parrot embryogenesis, the motor axon bundles are detectable within the muscular tissue only after the basic shape of the muscular tissue has been established. This supports the view that nervous tissue does not primarily determine the spatial pattern of jaw muscles. In contrast, the trigeminal motor nucleus, which is composed of somata of neurons that innervate major jaw muscles, of parrot is more developed compared to quail, even in embryonic stage where no remarkable interspecific difference in both jaw muscle morphology and motor nerve branching pattern is recognized. Our data suggest that although nervous tissue may not have a large influence on initial patterning of jaw muscles, it may play an important role in subsequent growth and maintenance of muscular tissue and alterations in cranial nervous tissue development may underlie diversification of jaw muscle morphology. J. Morphol. 275:191–205, 2014. © 2013 Wiley Periodicals, Inc.